Sedimentary basin formation associated with a silicic large igneous province: stratigraphy and provenance of the Mesoproterozoic Roopena Basin, Gawler Range Volcanics. Issue 4 (19th May 2018) - Curtis, S.; Wade, C.; Reid, A.
ABSTRACT: The Mesoproterozoic Gawler Silicic Large Igneous Province (SLIP) in the Gawler Craton and Curnamona Province, southern Australia, comprises extensive felsic and lesser mafic volcanic sequences, with only limited sedimentary successions. The Roopena Basin is a rare example of a synvolcanic sedimentary basin that formed within the Gawler SLIP in the eastern Gawler Craton. It is a north–south-trending basin with a preserved area of 75 km 2, bound by the Roopena and Wizzo Well faults, and contains three units of the lower Gawler Range Volcanics; the Angle Dam Dacite, Fresh Well Formation and Roopena Basalt. The Angle Dam Dacite is a porphyritic lava and the oldest part of the volcanic succession, directly overlying basement. The Fresh Well Formation overlies the Angle Dam Dacite or basement, comprises three coarsening-upwards volcaniclastic packages of claystone, siltstone, fine-grained to coarse-grained lithic sandstone and conglomerate deposited in a fluvio-lacustrine setting, and contains three tuff members. The Roopena Basalt is interlayered with the Fresh Well Formation, and comprises auto-brecciated lavas that exhibit only local interaction with water or wet sediment. Sharp basal contacts of the prograding packages within the Fresh Well Formation provide evidence of rapid flooding events within the basin. New detrital zircon geochronology of a sandstone within the Fresh Well Formation yielded a maximum depositional age of ca 1580 Ma, with provenance dominated by felsic volcanic units of the 1635–1605 Ma St Peter Suite. Sedimentation in the Gawler SLIP appears to have occurred in isolated basins with limited areal extent. It was largely restricted to the eastern Gawler Craton, and as well as the Roopena Basin, and includes similar basins at the Olympic Dam and Prominent Hill iron oxide–copper–gold ± uranium (IOCG ± U) deposits. The coincidence of sedimentation and mafic volcanism in the eastern Gawler Craton suggests that this region underwent extension at this time, although high-temperature metamorphism and compressional deformation occurred in some parts of the Gawler Craton and Curnamona Province synchronous with the Gawler SLIP. The Roopena Basin sedimentary rocks and underlying basement contain hematite–chlorite–sericite–white mica assemblages, permissive of hematite-style IOCG mineral deposits; however, no significant ore deposit has yet been discovered in the Roopena Basin.